Ottoman Architecture: Spatial Planning and Ideal Geometric Proportions (Case Study: Sultan Bayezid II Mosque) - Al-Mughrabi, Naser Thabet (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
One of the primary design tools Ottoman architects employed in the creation of their buildings and planning architectural spaces was geometric proportions. The Sultan Bayezid II Mosque in Istanbul, which was designed in a very distinctive geometric way but hasn't been thoroughly studied and discussed by researchers before, is a perfect example of how to apply geometric proportions. Thus, the primary objective of this study is to investigate the optimal geometric proportions that guided the construction of the mosque's plans and interior spaces. The architectural significance of the mosque in the history of Ottoman architecture is highlighted in this study, which employs a historical and analytical research method. After that, the architectural drawings were examined geometrically to demonstrate the proportions on which the mosque was constructed. The proportional shapes explored in the mosque's drawings confirmed that ideal geometric proportions were of great value in the minds of the engineers and architects who designed the mosque. The study's findings further support the mosque's architectural significance and geometric richness.